The Use of Combined Hip Arthroscopy and Periacetabular Osteotomy for Hip Dysplasia Is Increasing and Has Low Complication Rates - Juan Serna, B.S; Kira Furie, B.S; Stephanie E. Wong, M.D; Ishaan Swarup, M.D; Alan L. Zhang, M.D; Mohammad Diab, M.D (Elsevier, 2024)
Purpose: To analyze the annual use of hip arthroscopy (HA) and Bernese periacetabular osteotomy (PAO) for the treatment of hip dysplasia (HD), as well as postoperative outcomes, including ipsilateral reoperations. Methods: International Classification of Diseases, Ninth and Tenth Revision, codes were used to query the PearlDiver Mariner database from January 2010 through January 2022 to identify patients aged 10 to 59 years who had a presenting diagnosis of HD and subsequently underwent (1) HA; (2) PAO; or (3) combined HA and PAO (HA-PAO, defined as PAO on the same day or within 28 days after HA). We analyzed annual rates for each treatment, as well as rates of postoperative emergency visits, readmissions, and 5-year ipsilateral secondary operations (determined via Kaplan-Meier analysis). Results: There were 32,068 patients who underwent surgical treatment of HD. For HA, PAO, and HA-PAO, there were 29,700, 2,083, and 285 patients, respectively. All operations had the greatest percent-increase from 2015 to 2016. HA and HA-PAO peaked in 2021, whereas PAO peaked in 2019. For HA, PAO, and HA-PAO, most cases were performed in female patients and patients aged 30 to 49 years, 10 to 19 years, and 10 to 29 years, respectively. The 5-year incidence of ipsilateral secondary operations, which include revision HA, PAO, or conversion to total hip arthroplasty, was 9.2% (95% confidence interval 8.6%-9.8%) in the HA group and 6.5% (95% confidence interval 4.1%-8.8%) in the PAO group. Combining HA with PAO resulted in so few secondary operations that Kaplan-Meier analysis was infeasible. The PAO cohort had the greatest 30-day emergency visit and 90-day readmission rates, with infection as the most common cause for readmission. Conclusions: HA is more frequently performed than PAO for hip dysplasia. HA-PAO is increasing at the greatest rate, demonstrating fewer complications and reoperations. Level of Evidence: Level III, retrospective comparative trial.